2019
DOI: 10.1038/s41612-019-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

The Cape Town “Day Zero” drought and Hadley cell expansion

Abstract: In early 2018, Cape Town (population ~3.7 million) was at risk of being one of the first major metropolitan areas in the world to run out of water. This was due to a severe multi-year drought that led to the levels of supply dams falling to an unprecedented low. Here we analyze rainfall data from the city catchment areas, including rare centennial records from the surrounding region, to assess the severity of the 2015–2017 drought. We find that there has been a long-term decline in the number of winter rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
105
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 36 publications
17
105
2
1
Order By: Relevance
“…Doyle and Barros 2002 ; Reboita et al 2010 ), Southern Africa (e.g. Burls et al 2019 ). Understanding how SAs will respond under global warming condition is a crucial element of future climate projections for these regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doyle and Barros 2002 ; Reboita et al 2010 ), Southern Africa (e.g. Burls et al 2019 ). Understanding how SAs will respond under global warming condition is a crucial element of future climate projections for these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, using observed and reanalysis datasets, show that there is a significant SLP trend in recent decades in the SH subtropical regions (Gillett et al 2003 ; Gillett and Stott 2009 ; Grise et al 2018 ; Staten et al 2018 ; Vizy et al 2018 ; Burls et al 2019 ). The area and intensity of the SH SAs have increased in strength and extended towards the pole during both summer and winter seasons.…”
Section: Introductionmentioning
confidence: 99%
“…5 of Blamey et al 2018a ). In February 2018, the Western Cape Province was declared a disaster area after a severe drought which occurred between 2015 and 2018 (Pienaar and Boonzaaier 2018 ; Sousa et al 2018 ; Mahlalela et al 2019 ; Burls et al 2019 ). In October 2019, the Eastern Cape Province (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Burls et al . (2019) linked the drought to a long‐term decrease in rainfall events during cold fronts over the Western Cape region. They associated these changes in rainfall characteristics to Hadley Cell expansion over the Southern Hemisphere and to the upward trend in high‐pressure conditions in days following the passage of a frontal system.…”
Section: Introductionmentioning
confidence: 99%